Diffusion of White – Collar Crime in Transitional Contexts: Insurance Companies and Organised Crime - Bulatović, Aleksandra (Zbornik Instituta za kriminološka i sociološka istraživanja, 2008)
One of the simplest and most effective ways to launder large amounts of criminal funds is their channeling through an illegal scheme of insurance policy sales by foreign insurance companies, in other countries where foreign insurance is illegal. Given that in such circumstances insurance policies cannot be bought through legitimate financial transfers, large insurance companies have set up a wide network of dealers, who have been active for decades throughout the southeastern European region. They have operated by selling foreign insurance policies to the citizens of southeastern European countries, despite the fact that such policies have been entirely legally void in the region, and have subsequently taken large amounts of cash over the borders to the countries of origin of the insurance companies. Subsequently, policies bought in such a way have largely been legalized by the setting up of the insurance companies’ sister companies within the southeastern European region, and transferring these policies to such sister-companies, with the blessing of the National Banks of the region’s countries. While most policies bought in the described way have been clean, there is a possibility that some, namely those in the hundreds of thousands Euro per year, have included a very easy and effective manner of money laundering. This might have been the first step of a money laundering operation that has already happened and that cannot be effectively addressed at this stage. However, the second step of the process is still left to be performed, and that may be the investment of such large amounts by the foreign insurance companies in the privatization of state-owned enterprises in the region. The author argues in this article that, while the work of foreign insurance companies should be encouraged in the region, including Serbia, the potential second step of money laundering should be particularly closely monitored, specifically in situations when foreign insurance companies, which have been known to operate an illegal network of dealers in the previous period, appear as potential investors in the privatizations. While they should not be excluded from investment, they should be subject to thorough checking to try and prevent the particularly malignant forms of money laundering, namely the placement of the funds once siphoned out of the country in totally intransparent ways, back in the country through the taking over of controlling packages of parts of the local infrastructure.